Kepadatan dan Keanekaragaman Teripang (Holothuroidea) di Perairan Letman, Maluku Tenggara - Rosita Silaban; Jusron Ali Rahajaan; Munawir Hasan Ohoibor (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
The economic value of sea cucumbers is high in the market and is similar to other fishery commodity products. The high economic value causes the fishing effort to increase. The level of fishing that is not balanced with the availability of resources can threaten the existence of the population. This study aims to examine the density, size distribution, distribution pattern, population presence and growth pattern of sea cucumbers in Letman waters. The sampling method is a random method. The sea cucumbers found at the research site consisted of 8 species with a density range of 0.04-0.24 ind/m2. The results of measurements of temperature, salinity and pH at the study site obtained temperatures ranging from 29-31°C, salinity ranging from 28-31‰ and pH ranging from 8.11-8.26. The length of the sea cucumbers ranges from 10.5-31.52 cm, the diameter size ranges from 3.00-10.03 cm and the weight size ranges from 51.5-611.09 gr. The distribution pattern of sea cucumbers is grouped with an Id value of 1.23. The existence of sea cucumbers showed a low diversity value (H' = 0.42), low uniformity (E = 0.234) and the dominance was classified as stable (C = 0.83). The growth pattern of sea cucumbers obtained a b value of 2.16 so that it is classified as negative allometric (b < 3).